Cancer stem cell-immune cell crosstalk in the tumor microenvironment for liver cancer progression - Ma, Yue; Lv, Hongwei; Xing, Fuxue; Xiang, Wei; Wu, Zixin; Feng, Qiyu; Wang, Hongyang; Yang, Wen (Frontiers of medicine, 2024)
Crosstalk between cancer cells and the immune microenvironment is determinant for liver cancer progression. A tumor subpopulation called liver cancer stem cells (CSCs) significantly accounts for the initiation, metastasis, therapeutic resistance, and recurrence of liver cancer. Emerging evidence demonstrates that the interaction between liver CSCs and immune cells plays a crucial role in shaping an immunosuppressive microenvironment and determining immunotherapy responses. This review sheds light on the bidirectional crosstalk between liver CSCs and immune cells for liver cancer progression, as well as the underlying molecular mechanisms after presenting an overview of liver CSCs characteristic and their microenvironment. Finally, we discuss the potential application of liver CSCs-targeted immunotherapy for liver cancer treatment.